Factors influencing the performance of a public private partnership in the digital services sector - Abdallah, Wahid; Khan, M. Wasiqur Rahman; Prabhu, Jaideep (https://bigd.bracu.ac.bd/publications/factors-influencing-the-performance-of-a-public-private-partnership-in-the-digital-services-sector/, 2022)
The paper empirically investigates the performance of a Public-Private-Partnership initiative to spread public digital services in Bangladesh. The government established digital centres, run by two-member private entrepreneurial teams, in unions, the lowest administrative tier, throughout the country starting in 2007. The paper utilized a unique census data-set to examine three performance indicators, namely income, public service delivery and outreach. It found that private investment, cooperation from the local public oﬃcials and political representative, location of the centre, internet knowledge of the entrepreneur(s) and gender composition of the entrepreneurial team have important bearings on the performance indicators. Overall, the paper concluded with certain policy implications. First, since investment is an important determinant for all the performance indicators, the government may take steps to improve access to liquidity for entrepreneurs. Second, the UP Chair and UP Secretaries may be empowered to provide more direct assistance to UDC entrepreneurs for the betterment of performances. Third, the government may engage in more promotional activities if it would like to spread more of its services to the citizens. Fourth, the UDCs should be allowed space on the ground floor of UP compounds since it is shown that other locations lead to poorer performances. Finally, the government should think more carefully about how to make one-female-one-male teams more successful and encourage female entrepreneurs to stay in the workplace.